Influence of C and N on Strain-Induced Martensite Formation in Fe-15Cr-7Mn-4Ni-0.5Si Austenitic Steel - Caroline Quitzke (MDPI AG, 2021)
In this study, the effect of interstitial contents on the mechanical properties and strain-induced martensite formation in an austenitic stainless steel was investigated. The mechanical properties of solution annealed Fe-15Cr-7Mn-4Ni-0.5Si-(0.01-0.2)N-(0.01-0.2)C concentrations in weight percent stainless steels were studied using room temperature tensile tests. All three alloys used in the present study have a sum content of C + N of about 0.2 wt.%. To verify the influence of C and N on deformation behavior, microstructural investigations are performed using light optical microscopy, scanning electron microscopy, and magnetic and hardness measurements. Moreover, strain-induced α′-martensite nucleation was characterized by scanning electron microscope using EBSD. In the present alloy system, carbon provides a stronger austenite stabilizing effect than nitrogen. Hence, the smallest amount of strain-induced α′-martensite was formed in the steel alloyed with 0.2 wt.% C. It also exhibited the optimal mechanical properties, including the highest ultimate tensile strength (1114 MPa), uniform elongation (63%), and total elongation (68%). Moreover, the interstitial content influences the occurrence of dynamic strain aging (DSA), which was only observed in the steel alloyed with carbon. With increasing C content, the triggering strain for DSA decreases, which can be confirmed by in situ magnetic measurements during tensile testing.